Hubungan antara Burden of Care dan Burnout pada Family Caregiver Orang dengan Demensia - Reynerly Wijaya; Lie Fun Fun (Humanitas (Jurnal Psikologi), 2022)
Individuals with dementia (IWD) need a caregiver, usually their own family, to take care of them. Family caregiver often have others role beside being a caregiver. Therefore, family caregiver will involve in many high pressure situation, which can be perceive as burden of care. Burden of care can be a risk of burnout. This research used burden of care theory by Zarit (1986) and burnout theory  by Maslach (2003). Sample in this research are 40 IWD’s  family caregiver in Alzheimer Community. This sample collected using purposive sampling technique. The research instruments were MBI-HSS questionnaire (validity: 0.364-0.832; reliability: 0.91) and ZBI-12 questionnaire (validity: 0.325-0.905; reliability: 0.926). The two questionnaires were modified to fit the participant’s characteristics. Both questionnaires were correlated using correlation test of spearman’s rho with  SPSS 23 to find out the relationship between burden of care and burnout. Based on this test, correlation coefficient score of 0.899 with p=0.00 was achieved. This result shows that there is a significant positive correlation between burden of care and burnout experienced by the family caregiver in the Alzheimer Community. In this research, sex was the only sociodemography variable that correlated with burnout.